This is going to hurt secret diaries of a junior doctor - Kay, Adam (London Picador, cop, 2018)
The often hilarious, at times horrifying and occasionally heartbreaking diaries of a former junior doctor, and the story of why he decided to hang up his stethoscope
1
Keywords: Kay, Adam-- Zdravniki; pacienti -- anekdote